GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 308 species occurrences available in GBIF matching the query: TaxonKey: Rosa coriifolia O. Bolòs & Vigo BasisOfRecord: Specimen or Living Specimen. The dataset includes 308 records from 30 constituent datasets: 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from SANT herbarium vascular plants collection. 1 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 1 records from Tallinn Botanic Garden. 32 records from Estonian Museum of Natural History. 40 records from Estonian University of Life Sciences. 3 records from Tiroler Landesmuseum Ferdinandeum. 2 records from Tropicos Specimen Data. 3 records from Natural History Museum (London) Collection Specimens. 1 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 3 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 24 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 1 records from Herbario de la Universidad de Sevilla. 3 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 1 records from Institut Botanic de Barcelona, BC. 1 records from The Erysiphales Collection at the Botanische Staatssammlung München. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 18 records from Natural History Museum, University of Tartu. 8 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 143 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from SBT-Living. 2 records from Herbier du Muséum Henri-Lecoq de Clermont-Ferrand - Rosacées. 3 records from Botany (UPS). 2 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5 records from SysTax - Botanical Gardens. 2 records from Herbarium specimens of CBNA (GAP). 1 records from SysTax - Herbaria.
Keywords: GBIF; biodiversity; species occurrences